Wiman type inequalities for entire Dirichlet series with arbitrary exponents - A. O. Kuryliak; I. Ye. Ovchar; O. B. Skaskiv (Математичні Студії, 2013)
We prove analogues ofthe classical Wiman inequality for entire Dirichlet series$f(z)=sum_{n=0}^{+infty}a_ne^{zlambda_n}$ with arbitrary positiveexponents $(lambda_n)$ such that$sup{lambda_ncolon ngeq 0 }=+infty$.